2018
DOI: 10.1002/prca.201700153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Proteins Involved in Autoimmune Cirrhosis and Normal Serum by iTRAQ Proteomics

Abstract: These findings offer a comprehensive profile of the AIC proteome about candidate biomarkers and provide a useful basis for further analysis of the pathogenic mechanism of AIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In hepatitis C, ubiquitylation and proteasomal degradation of retinoblastoma protein (pRb) with concomitant E2F transcription factor release and cellular proliferation can contribute to the disease progression and development of hepatocellular carcinoma [ 22 ]. Our results are also in line with a study, which, after proteomic analysis, revealed a possible implication of dysfunctional vesicle-mediated transport in the pathogenesis of AIH [ 23 ].…”
Section: Resultssupporting
confidence: 92%
“…In hepatitis C, ubiquitylation and proteasomal degradation of retinoblastoma protein (pRb) with concomitant E2F transcription factor release and cellular proliferation can contribute to the disease progression and development of hepatocellular carcinoma [ 22 ]. Our results are also in line with a study, which, after proteomic analysis, revealed a possible implication of dysfunctional vesicle-mediated transport in the pathogenesis of AIH [ 23 ].…”
Section: Resultssupporting
confidence: 92%
“…Currently, there are no studies that have investigated the expression of these proteins in tissue biopsies or biological fluids of PSC patients. Nevertheless, an increased liver content of core histone macro-H2A.1 has been identified in murine models of hepatic steatosis [41] and fat-associated hepatocellular carcinoma [42], and an upregulation of immunoglobulin lambda variable 3-19 has been shown in the serum samples of 16 patients with autoimmune cirrhosis compared to the healthy control group [43]. Although saliva is not considered functionally associated with the bile ducts, some of the identified DEPs, such as disulfideisomerase A3, exhibited a clear deregulation in the bile and serum of PSC patients [20], confirming saliva as potential biological fluid in PSC characterization.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out mass spectrometric analysis as previously reported [ 18 ]. The iTRAQ-tagged peptide was reconstituted and loaded onto Phenomenex columns (Gemini-NX 3u C18 110 A; 150*2.00 mm) using a Dionex UltiMate 3000 HPLC system (A-phase: 20mM HCOONH4, PH 10, B-phase: 20mM HCOONH4, 98%CAN, PH 10).…”
Section: Methodsmentioning
confidence: 99%